Simulation and skill training facilities in nursing institutes at Uttarakhand: A cross-sectional study - Garima Goswami; Suresh K Sharma; Rakesh Sharma; Ritu Rani (Wolters Kluwer Medknow Publications, 2021)
Background: Simulation and skill development facilities are essential for the training and preparation of nursing students, which aids in their clinical readiness and professional development. The aim of the study was to assess simulation and skill training facilities, their utility in selected nursing institutes at Uttarakhand. Materials and Methods: This descriptive cross-sectional study was conducted in conveniently selected 16 nursing institutes at Uttarakhand (India). Data were collected from Nov. to Dec. 2019, through a face-to-face interview using a validated self-structured questionnaire. Descriptive and inferential statistics were used to analyze the data. Results: There were 16 institutes from four districts that participated in the study. Of these, five (31%) were government, and 11 (69%) were private. All nursing institutes (100%) had a nursing foundation lab, midwifery, and child health nursing lab, while only 44% of institutes had a medical surgical nursing skill lab. Among skill development facilities, the overall average number [mean (SD)] of mannequins was 3.90 (7.10); and high-fidelity simulators were 2.47 (7.1). In private institutes, the average period [mean (SD)] of laboratory usage was significantly higher than in government institutes [35.82 (6.57) vs 27.40 (5.22); p = 0.025]. The duration of lab usages was significantly associated with the age of the institute (p = 0.04). Conclusions: This study found inadequate simulation and skills training facilities and less utilization of those facilities. There is a great need to find out the key issues that lead to the unavailability and limited use of the required nursing skill development facilities.